Ginsenoside Rd reduces cell proliferation of non-small cell lung cancer cells by p53-mitochondrial apoptotic pathway - Xilin Wan; Xin Jin; Xinmin Wu; Dan Dong; Hongmei Yang; Renbo Tan; Ying Sun; Xinze Liu; Kaijing Sun; Wei Wu; Changbao Chen (Heliyon, 2024)
Ginsenoside Rd is a tetracyclic triterpenoid derivative, widely existing in Panax ginseng, Panax notoginseng and other traditional Chinese medicines. Many studies have proved that ginsenoside Rd have a variety of significant biological activities on certain types of cancer. However, the mechanism of ginsenoside Rd remains unclear in lung cancer. The findings of this study reveal that GS-Rd inhibits the proliferation of NSCLC cells, induces apoptosis, and suppresses migration and invasion. The results showed Ginsenoside Rd inhibited the cell proliferation (∼99.52 %) by S phase arrest in cell cycle and promoted the apoptosis (∼54.85 %) of NSCLC cells. It also inhibited the migration and invasion of cells (p < 0.001). The expression levels of related mitochondrial apoptosis proteins (Bax/Bcl-2/Cytochrome C) and matrix metalloproteinases (MMP-2/-9) were significantly changed. The results showed that ginsenoside Rd inhibited the proliferation of tumor cells by activating p53/bax-mediated mitochondrial apoptosis and the expression of key enzymes for cell apoptosis caspase-3/cleaved-caspase-3 were significantly increased. This research contributes to a better understanding of the anti-tumor effects and molecular mechanisms of GS-Rd, paving the way for its potential development and clinical application in NSCLC therapy.